Relasi Gender Antar Anggota Keluarga: Pengalaman Tiga Perempuan dalam Perspektif Agama dan Perubahan Sosial - Syamsiyatun, Siti (Musawa Jurnal Studi Gender dan Islam, 2004)
During the course of women's movement history in Indonesia since a century ago, 'educated' women have had assumed significant roles. They have become one of the most important agents to promote social changes in Indonesian community, particularly in the areas affecting women's standing in society, such as improving and extending education, women's representation in the parliament, challenging the practice of child marriage and women in the work force. This paper attempts to portray women's empirical experiences in dealing with their domestic affairs with particular emphasis given to the nature of their gender relationships with husband and parents in law. The women participating in this preliminary study do not represent the 'working class' who has limited qualifications in terms of training and professional skills. Far from those characteristics, they all hold higher degree in education and have stable career as professionals. Based on several series of interviews, the study finds that while the women have achieved greater social and economic status and independency within their public life, the condition of the gender relation within the confine of family household remains the same. It is found that women have been assigned greater responsibility for maintaining the relationships within their own immediate family as well as with their in laws'. Not only do these women experience double burdens, they are exposed to multi burdens, in terms of gender relations with their in laws.